PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR PENGGERAK - Faradiba, Salsa Ayu; Nurhasanah, Ana; Pribadi, Reksa Adya (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
Currently, the world of education is facing a major challenge, namely preparing students to confront the demands of globalization. This challenge has led to various issues, such as student brawls, a decline in respect for parents and teachers, weakened sense of responsibility, increased dishonesty, moral degradation, and bullying—all of which must be addressed. The low character development among students is attributed to an educational focus that emphasizes cognitive aspects over character formation. This study aims to examine the planning, implementation process, and results of the Pancasila Student Profile Strengthening Project. The study uses a qualitative descriptive approach, with data collected in the form of words and images. The participants consisted of 25 people, including 1 principal, 2 fourth-grade teachers, and 23 fourth-grade students. The results indicate that the Pancasila Student Profile Strengthening Project, as conducted by the teachers, was implemented in accordance with the plans outlined in the project module, and the outcomes have developed in alignment with the dimensions of the Pancasila Student Profile.